Hydrophilic high-flux aluminum-based lithium sorbent hollow fiber particles, methods of making and using the same

CN122974203APending Publication Date: 2026-10-27EAST CHINA UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611179321.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-05
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

但是纺丝成型工艺对各项参数的调控精度要求严苛,且纺丝成型吸附剂的机械强度显著低于聚合成型和粘结成型吸附剂颗粒

Benefits of technology

1.本发明提供的铝基锂吸附剂为中空柱状颗粒,粒径可控在0.5~2 mm,内部贯通中空通道搭配疏松多孔内壁,大幅缩短锂离子从颗粒外部扩散至内部吸附活性位点的扩散路径。流体可直接贯穿中空内腔,消除实心颗粒内部传质死区,离子扩散阻力显著降低,吸附动力学速度大幅提升,远优于传统实心成型吸附剂。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122974203A_ABST
    Figure CN122974203A_ABST
Patent Text Reader

Abstract

The application discloses a preparation method of hydrophilic high-flux aluminum-based lithium adsorbent hollow fiber particles, comprising the following steps: S1. uniformly stirring aluminum-based lithium adsorbent precursors in an ionic dispersant aqueous solution, washing and dispersing the aluminum-based lithium adsorbent precursors by using a water-soluble organic solvent after filtration, drying and screening the solid-liquid separated product to obtain high-dispersibility aluminum-based lithium adsorbent precursor powder; S2. dissolving a non-water-soluble polymer, a water-soluble polymer and a coupling agent in a water-soluble organic solvent, and stirring under heating to obtain a binder solution; S3. uniformly mixing the high-dispersibility aluminum-based lithium adsorbent precursor powder and the binder solution to obtain a molding slurry; and S4. extruding or spinning the molding slurry into a coagulation bath for solidification, then immersing the product in a protective liquid, and cutting the product to obtain the hydrophilic high-flux aluminum-based lithium adsorbent hollow fiber particles. The aluminum-based lithium adsorbent hollow fiber particles prepared by the molding method have high hydrophilicity, high mass transfer efficiency and good cycle stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of powder molding and granulation technology, specifically to a hydrophilic high-throughput aluminum-based lithium adsorbent hollow fiber particles, its preparation method, and its application. Background Technology

[0002] Lithium is widely distributed in nature, but due to its high reactivity, it usually exists in compound form. Lithium resources are mainly distributed in lithium ores and salt lake brines. Compared with lithium extraction from ores, lithium extraction from brines has lower production costs and difficulty, and also has less environmental impact.

[0003] my country's lithium resources are mainly found in salt lake brines, characterized by a high magnesium-to-lithium ratio and low lithium grade. Adsorption methods, due to their lower requirements in brine pretreatment, high selectivity and recovery rate for lithium ions, and cost-effectiveness and environmental friendliness, have been widely adopted in the salt lake lithium extraction industry. Common lithium-ion adsorbents include manganese-based and titanium-based ion sieves, as well as aluminum-based lithium adsorbents. However, manganese-based and titanium-based ion sieves suffer from severe dissolution during acid washing and regeneration, limiting their application to large-scale industrial production. Further research is needed to overcome these bottlenecks. Aluminum-based lithium adsorbents, on the other hand, spontaneously desorb in neutral solutions, preventing dissolution during lithium extraction and enabling long-term stable lithium extraction. They have become the widely used adsorbents in industry.

[0004] In continuous lithium extraction in a fixed bed, aluminum-based lithium adsorbent powders are prone to increased bed pressure drop and blockage due to poor flowability and low permeability. To address these issues, industrially, a strategy of combining polymer binders with powders is commonly employed to prepare molded materials with specific morphologies exhibiting excellent flowability and permeability. The binder molding method is currently the most mature application process. It involves encapsulating the powder adsorbent with a specialized binder to obtain millimeter-sized particles with a certain mechanical strength. However, these molded particles have inherent defects, including low internal porosity. The polymer matrix easily covers the active sites of the adsorbent and blocks the pores, leading to a significant decrease in mass transfer rate and adsorption capacity. Furthermore, the powder is prone to agglomeration and uneven dispersion within the binder, further reducing the effective utilization rate of the adsorbent. Spinning is another commonly used method in the molding field. Its principle involves extruding a spinning solution prepared by combining polymers and powder adsorbents through a spinneret to form a fine stream. This stream then enters a coagulation bath system for solidification, ultimately forming a fibrous lithium adsorbent. However, the spinning process requires strict control of various parameters, and the mechanical strength of the spun adsorbent is significantly lower than that of the polymerized and bonded adsorbent particles. Summary of the Invention

[0005] The purpose of this invention is to provide a method for preparing hollow fiber particles of hydrophilic high-flux aluminum-based lithium adsorbent. The aluminum-based lithium adsorbent particles prepared by this molding method have high hydrophilicity, high mass transfer efficiency and good cycle stability.

[0006] In a first aspect, the present invention provides a method for preparing hydrophilic high-flux aluminum-based lithium adsorbent hollow fiber particles, comprising the following steps: S1. The aluminum-based lithium adsorbent precursor is stirred evenly in an aqueous solution of an ionic dispersant, filtered, washed and dispersed with a water-soluble organic solvent, and after solid-liquid separation, dried and sieved to obtain a highly dispersible aluminum-based lithium adsorbent precursor powder. S2. Dissolve the non-water-soluble polymer, the water-soluble polymer, and the coupling agent in a water-soluble organic solvent, heat and stir until completely dissolved to obtain an adhesive solution; S3. The highly dispersible aluminum-based lithium adsorbent precursor powder is mixed with the binder solution to obtain a molding slurry; S4. The molding slurry is extruded through an extrusion molding device or spun into a coagulation bath through a wet spinning molding device and then solidified. After being immersed in a protective liquid and granulated, hydrophilic high-flux aluminum-based lithium adsorbent hollow fiber particles are obtained; wherein, the coagulation bath is an aqueous solution containing a crosslinking agent, lithium salt and micro-nano bubbles.

[0007] Further, in step S1 of the present invention, the aluminum-based lithium adsorbent is chemically represented as mLiCl·2Al(OH)3·nH2O, where m is 0.2~1 and n is 0.5~10. This aluminum-based lithium adsorbent precursor is prepared by co-precipitation of a lithium source and an aluminum source in an alkaline solution.

[0008] Furthermore, in step S1 of the present invention, the aluminum-based lithium adsorbent precursor is pretreated sequentially with an ionic dispersant and a water-soluble organic solvent, which can improve the dispersion performance of the adsorbent powder, avoid a large amount of agglomeration when the powder is mixed with the binder, and ensure the full exposure and effective utilization of the adsorption active sites.

[0009] Further, in step S1 of the present invention, the ionic dispersant includes, but is not limited to, one or more of sodium polyphosphate, sodium polyacrylate, sodium dodecylbenzenesulfonate, sodium oleate, fumaric acid, and maleic acid. In the aqueous solution of the ionic dispersant, the mass fraction of the ionic dispersant is preferably 0.1% to 10%, for example, 0.1%, 0.2%, 0.3%, 0.4%, 0.8%, 1.0%, 2.0%, 3.0%, 4.0%, 5.0%, 6.0%, 8.0%, 10.0%, etc.

[0010] Further, in step S1 of the present invention, the ratio of the aluminum-based lithium adsorbent precursor to the aqueous solution of the ionic dispersant is preferably 0.002~0.5 g / mL, for example, it can be 0.002 g / mL, 0.004 g / mL, 0.005 g / mL, 0.008 g / mL, 0.01 g / mL, 0.02 g / mL, 0.05 g / mL, 0.08 g / mL, 0.1 g / mL, 0.2 g / mL, 0.3 g / mL, 0.4 g / mL, 0.5 g / mL, etc.

[0011] Further, in step S1 of the present invention, the stirring rate is preferably 200~1000 rpm, for example, 200 rpm, 400 rpm, 500 rpm, 600 rpm, 1000 rpm, etc.; the stirring temperature is preferably 20~90℃, for example, 20℃, 30℃, 40℃, 50℃, 60℃, 70℃, 80℃, 90℃, etc.; the stirring time is preferably 0.5~4 hours, for example, 0.5 hours, 1 hour, 2 hours, 3 hours, 4 hours, etc.

[0012] Furthermore, in steps S1 and S2 of the present invention, the water-soluble organic solvent includes, but is not limited to, one or more of formamide, N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone, dimethyl sulfoxide, tetrahydrofuran, methanol, ethanol, and acetone.

[0013] Furthermore, in step S2 of this invention, using a non-water-soluble polymer and a water-soluble polymer as a mixed binder to bond the aluminum-based lithium adsorbent powder allows the adsorbent to possess both high mechanical strength and hydrophilicity. The non-water-soluble polymer is one or more of polyvinyl chloride, polyvinylidene fluoride, polystyrene, polyacrylonitrile, polymethyl methacrylate, polyethersulfone, and polylactic acid; the water-soluble polymer is one or more of polyacrylamide, polyhydroxyethyl methacrylate, polydimethylaminoethyl methacrylate, gelatin, and carboxymethyl cellulose.

[0014] Furthermore, in step S2 of this invention, adding a coupling agent during the preparation of the binder solution can enhance the interaction between the inorganic aluminum-based lithium adsorbent powder precursor and the polymer binder, ensuring that the adsorbent powder is uniformly dispersed during the molding process and forms a stable bonding interface with the binder, thereby improving the structural stability of the adsorbent particles. The coupling agent is one of silane coupling agents, titanate coupling agents, aluminate coupling agents, or phosphate coupling agents.

[0015] Furthermore, in step S2 of the present invention, the preferred addition ratio of the non-water-soluble polymer, the water-soluble polymer, the coupling agent and the organic solvent is 0.01~0.5 g: 0.01~0.5 g: 0.01~0.2 g: 0.001~0.01 g: 1 mL.

[0016] Furthermore, in step S2 of the present invention, the heating temperature during the preparation of the adhesive solution is preferably 40~100℃, for example, 40℃, 50℃, 60℃, 70℃, 80℃, 90℃, 100℃, etc. This temperature can ensure that the non-water-soluble polymer and the water-soluble polymer are fully dissolved in the organic solvent, thereby improving the uniformity of the adhesive solution.

[0017] Furthermore, in step S3 of the present invention, the ratio of the highly dispersible aluminum-based lithium adsorbent precursor powder to the binder solution is preferably 0.02~1 g / mL, for example, it can be 0.02 g / mL, 0.04 g / mL, 0.05 g / mL, 0.08 g / mL, 0.1 g / mL, 0.2 g / mL, 0.3 g / mL, 0.4 g / mL, 0.5 g / mL, 0.6 g / mL, 0.8 g / mL, 1.0 g / mL, etc.

[0018] Furthermore, in step S3 of the present invention, the mixing treatment includes one or more of mechanical stirring, ultrasonic dispersion and degassing treatment, wherein the ultrasonic dispersion time is preferably 30 to 120 min, for example, 30 min, 40 min, 50 min, 60 min, 80 min, 100 min, 120 min, etc.

[0019] During the mixing process, mechanical stirring is used to achieve the initial mixing of aluminum-based lithium adsorbent precursor powder and binder solution, ultrasonic dispersion is used to break up powder agglomerates and improve the dispersion uniformity of aluminum-based lithium adsorbent powder in binder system, and degassing treatment is used to remove macroscopic bubbles entrained in molding slurry to improve the stability of molding slurry and the continuity of subsequent molding process.

[0020] Furthermore, in step S4 of the present invention, in order to construct aluminum-based lithium adsorbent molded particles with a hollow structure, an extrusion molding device or a wet spinning molding device can be used to continuously extrude or spin the molding slurry. This not only controls the structure of the molded particles, but also improves the continuity and scale-up adaptability of the preparation process.

[0021] For example, in some embodiments, when the molding slurry is continuously extruded using an extrusion molding device (such as a screw extruder), a strip-shaped adsorbent preform with a hollow structure can be extruded through a specially designed extrusion die. In other embodiments, the molding slurry can be continuously spun using a coaxial spinning device, wherein the molding slurry serves as the shell layer solution and a lithium-ion solution serves as the core layer solution, and the fibers with a hollow structure are obtained by extrusion through a coaxial spinning nozzle.

[0022] Furthermore, in step S4 of the present invention, the coagulation bath can solidify the extruded strip-shaped preform or fiber with a hollow structure. The crosslinking agent in the coagulation bath crosslinks the water-soluble polymer in the mixed binder, forming a three-dimensional porous network structure, reducing swelling while improving overall mechanical strength and chemical stability. Further, the crosslinking agent includes, but is not limited to, one of citric acid, epichlorohydrin, tannic acid, tartaric acid, glutaraldehyde, borax, calcium ions, or iron ions, with a preferred mass fraction of 1% to 10%, for example, 1%, 2%, 3%, 4%, 5%, 6%, 8%, 10%, etc.

[0023] Furthermore, in step S4 of this invention, the role of the lithium salt in the coagulation bath is to inhibit the excessive deintercalation and intercalation of lithium in the internal structure of the adsorbent molding material when it comes into contact with water, thereby maintaining the stability of the crystal structure of the aluminum-based lithium adsorbent. The lithium salt in the coagulation bath includes, but is not limited to, one or more of lithium chloride, lithium nitrate, lithium sulfate, or lithium hydroxide, and its lithium ion concentration is preferably 100~500 mg / L, for example, 100 mg / L, 200 mg / L, 300 mg / L, 400 mg / L, 500 mg / L, etc.

[0024] Furthermore, in step S4 of the present invention, the role of micro- and nano-bubbles in the coagulation bath is to form microscale disturbances in the coagulation bath, which plays a regulatory role in the phase separation process of the fiber surface, thereby improving the surface pore structure of the formed fiber and facilitating the formation of a porous adsorbent forming material. The micro-nano bubbles can be generated by a micro-nano bubble generator and introduced into the coagulation bath. The operating pressure of the micro-nano bubble generator is 0.1~0.5 MPa, for example, 0.1 MPa, 0.2 MPa, 0.3 MPa, 0.4 MPa, 0.5 MPa, etc.; the gas flow rate is 0.1~2.0 L / min, for example, 0.1 L / min, 0.2 L / min, 0.5 L / min, 0.8 L / min, 1.0 L / min, 1.2 L / min, 1.5 L / min, 2.0 L / min, etc.; the liquid circulation flow rate is 1~10 L / min, for example, 1 L / min, 2 L / min, 3 L / min, 5 L / min, 8 L / min, 10 L / min, etc.; and the processing time is 1~30 min, for example, 1 min, 2 min, 5 min, 10 min, 20 min, 30 min, etc.

[0025] Furthermore, the micro-nano bubbles can include one or more of the following: air bubbles, oxygen bubbles, carbon dioxide bubbles, nitrogen bubbles, argon bubbles, and ozone bubbles. The diameter of the micro-nano bubbles is preferably 10–1000 nm, for example, 10 nm, 20 nm, 50 nm, 100 nm, 200 nm, 300 nm, 400 nm, 500 nm, 600 nm, 800 nm, 1000 nm, etc.

[0026] Furthermore, in step S4 of the present invention, the protective liquid is used to remove residual solvent on the surface of the adsorbent and simultaneously inhibit the precipitation of lithium ions. The protective liquid is a lithium salt solution, wherein the lithium salt is one or more of lithium chloride, lithium nitrate, lithium sulfate, or lithium hydroxide, and the lithium ion concentration is preferably 100~500 mg / L, for example, 100 mg / L, 200 mg / L, 300 mg / L, 400 mg / L, 500 mg / L, etc.

[0027] Furthermore, in step S4 of the present invention, the soaking time in the protective solution is preferably 0.5 to 4 hours, for example, 0.5 hours, 1 hour, 2 hours, 3 hours, 4 hours, etc. The soaking temperature in the protective solution is preferably 20 to 80°C, for example, 20°C, 30°C, 40°C, 50°C, 60°C, 70°C, 80°C, etc.

[0028] Furthermore, in step S4 of the present invention, the adsorbent, after being soaked in the protective solution, is granulated to obtain hydrophilic high-flux aluminum-based lithium adsorbent hollow fiber particles. The granulation method includes, but is not limited to, high-pressure micro-water flow granulation.

[0029] Secondly, the present invention provides hydrophilic high-flux aluminum-based lithium adsorbent hollow fiber particles prepared by the aforementioned method.

[0030] Thirdly, the present invention provides an application of the aforementioned hydrophilic high-flux aluminum-based lithium adsorbent hollow fiber particles to extract lithium from a lithium-containing solution, wherein the lithium-containing solution is preferably a lithium-containing solution with high magnesium, sodium, potassium and calcium content, specifically including but not limited to one or more of salt lake brine, seawater, geothermal brine, oil and gas field produced water, lithium battery recovery leachate or self-prepared lithium-containing solution.

[0031] Compared with the prior art, the beneficial effects of the present invention are as follows: 1. The aluminum-based lithium adsorbent provided by this invention is a hollow cylindrical particle with a controllable particle size of 0.5~2 mm. The internal hollow channels, combined with a loose, porous inner wall, significantly shorten the diffusion path of lithium ions from the outside of the particle to the internal adsorption active sites. Fluids can directly penetrate the hollow cavity, eliminating mass transfer dead zones inside solid particles, significantly reducing ion diffusion resistance, and greatly improving adsorption kinetics, far superior to traditional solid-shaped adsorbents.

[0032] 2. The aluminum-based lithium adsorbent provided by the present invention has a hollow structure in which the pore size, wall thickness and internal cavity size can be artificially adjusted. By changing the molding die, adjusting the spinning / extrusion parameters and the micro-nano bubble particle size, the internal pore structure of the particles can be precisely controlled, and it can be adapted to brine systems with different lithium concentrations and magnesium-lithium ratios.

[0033] 3. The aluminum-based lithium adsorbent provided by the present invention uses ionic dispersants and water-soluble organic solvents to pretreat the precursor, eliminating powder agglomeration at the source. It can achieve uniform dispersion of powder in binder without additional ball milling, avoiding local accumulation of active sites and local binding agent clogging of pores, maximizing the effective utilization rate of adsorbent powder, and further amplifying the adsorption performance advantages brought by hollow structure.

[0034] 4. The aluminum-based lithium adsorbent provided by this invention adopts a composite binding system of water-soluble polymer and non-water-soluble polymer. The water-soluble polymer endows the particles with excellent hydrophilic properties, and the brine can quickly wet the internal pores of the particles, resulting in higher liquid-phase mass transfer flux. The non-water-soluble polymer provides skeletal support, and the coupling agent strengthens the interfacial bonding force between the inorganic aluminum-based powder and the organic binder. The crosslinking agent forms a three-dimensional network during the solidification stage. The finished particles are resistant to swelling, wear, and water flow impact. They are not easily broken or pulverized when used in a fixed bed, and the bed pressure drop is stable.

[0035] 5. The aluminum-based lithium adsorbent provided by this invention introduces micro-nano bubbles in the coagulation bath to actively regulate the phase separation process, constructing a large number of interconnected pores in the particle wall layer. Combined with the precursor dispersion pretreatment process, it avoids adsorbent powder agglomeration, fully exposes the internal active sites, and significantly improves the overall specific surface area and porosity of the material, providing sufficient reaction sites for lithium ion adsorption.

[0036] 6. The aluminum-based lithium adsorbent provided by this invention has a wide range of applicable raw materials and can be used in high-impurity lithium solutions such as salt lake brine, seawater, geothermal brine, oil and gas field produced water, and lithium battery recycling leachate.

[0037] 7. The aluminum-based lithium adsorbent molding method provided by the present invention is simple to operate and easy to achieve large-scale production. Attached Figure Description

[0038] Figure 1 This is a photograph of the hollow particles of the aluminum-based lithium adsorbent prepared in Example 1.

[0039] Figure 2 The image shows the SEM image of the hollow particles in the aluminum-based lithium adsorbent prepared in Example 1.

[0040] Figure 3 The image shows the contact angle of the hollow particles in the aluminum-based lithium adsorbent prepared in Example 1.

[0041] Figure 4 The image shows the XRD patterns of the hollow particles of the aluminum-based lithium adsorbents prepared in Examples 1-3.

[0042] Figure 5 The simulation diagrams are for the different structures of adsorbents in Example 1 and Comparative Example 2.

[0043] Figure 6 The graph shows a comparison of the lithium-ion adsorption kinetics of the aluminum-based lithium adsorbent particles prepared in Examples 1-3 and Comparative Examples 1-4 in the old brine of Chaka Salt Lake.

[0044] Figure 7 The diagram shows the lithium-ion adsorption-desorption cycle of the hollow particles of the aluminum-based lithium adsorbent prepared in Examples 1-3. Detailed Implementation

[0045] The present invention will be further described below with reference to the accompanying drawings and specific embodiments, so that those skilled in the art can better understand and implement the present invention. However, the embodiments described are not intended to limit the present invention.

[0046] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains. The terminology used herein in the description of the invention is for the purpose of describing particular embodiments only and is not intended to be limiting of the invention. The term "and / or" as used herein includes any and all combinations of one or more of the associated listed items.

[0047] Unless otherwise specified, the experimental methods used in the following examples are conventional methods, and the materials and reagents used are commercially available.

[0048] Example 1 This embodiment provides a method for preparing hydrophilic high-flux aluminum-based lithium adsorbent hollow fiber particles, including the following steps: S1. An aluminum-based lithium adsorbent precursor was prepared by co-precipitation. The precursor powder was added to a 3% sodium dodecylbenzenesulfonate aqueous solution at a ratio of 60 mL / g and stirred at 60°C for 2 hours. After filtration, the mixture was washed and dispersed with ethanol at a liquid-to-solid ratio of 100 mL / g. After filtration, the mixture was dried at 60°C for 12 hours and then ground to obtain a highly dispersed aluminum-based lithium adsorbent powder. The highly dispersed aluminum-based lithium adsorbent precursor powder was passed through a 300-mesh sieve.

[0049] S2. Weigh 2 g of polyvinyl chloride, 2 g of polyacrylonitrile, 0.4 g of poly(dimethylaminoethyl methacrylate) and 0.1 g of aluminate coupling agent F-2, add them to 30 mL of N,N-dimethylformamide, heat and stir at 100℃ and 500 rpm until completely dissolved to prepare an adhesive solution.

[0050] S3. Weigh 12 g of highly dispersible aluminum-based lithium adsorbent powder from a 300-mesh sieve and mix it with the binder solution to prepare a spinning solution. Then, ultrasonically degas the spinning solution for 1 h. Prepare a 300 mg / L lithium ion solution as the spinning core solution.

[0051] S4. The spinning solution is injected into the supply tank of a wet spinning machine and extruded through a coaxial spinning nozzle with an outer needle inner diameter of 1.07 mm and an inner core outer diameter of 0.7 mm. The spun fibers are placed in a coagulation bath containing 1 wt% tannic acid and 300 mg / L lithium ions. Micro-nano bubbles are introduced through a bubble generator at a working pressure of 0.3 MPa, a gas flow rate of 0.8 L / min, a liquid circulation flow rate of 2 L / min, and a processing time of 10 min. The fibers are then soaked and cured for 12 h, with the supply tank and coagulation bath temperature maintained at 50℃. After pelleting at 30℃, hollow aluminum-based lithium adsorbent particles with a length of 1-3 mm are obtained. The formed hollow aluminum-based lithium adsorbent particles are rinsed three times with a 300 mg / L lithium ion solution to remove residual organic solvents.

[0052] Example 2 This embodiment provides a method for preparing hydrophilic high-flux aluminum-based lithium adsorbent hollow fiber particles, including the following steps: S1. An aluminum-based lithium adsorbent precursor was prepared by co-precipitation. The precursor powder was added to a 5% sodium polyphosphate aqueous solution at a ratio of 60 mL / g and stirred at 40°C for 2 hours. After filtration, the mixture was washed and dispersed with acetone at a liquid-to-solid ratio of 100 mL / g. After filtration, the mixture was dried at 60°C for 12 hours and then ground to obtain a highly dispersed aluminum-based lithium adsorbent powder. The highly dispersed aluminum-based lithium adsorbent precursor powder was then passed through a 300-mesh sieve.

[0053] S2. Weigh 2 g of polyvinylidene fluoride, 2 g of polyacrylonitrile, 0.4 g of poly(dimethylaminoethyl methacrylate) and 0.1 g of silane coupling agent KH550, add them to 30 mL of N,N-dimethylformamide, and heat and stir at 100℃ and 500 rpm until completely dissolved to prepare an adhesive solution.

[0054] S3. Weigh 12 g of highly dispersible aluminum-based lithium adsorbent powder from a 300-mesh sieve and mix it with a binder solution to prepare a spinning solution. Then, ultrasonically degas the spinning solution for 1 h. Prepare a 300 mg / L lithium ion solution as the spinning core solution.

[0055] S4. The spinning solution is injected into the supply tank of a wet spinning machine and extruded through a coaxial spinning nozzle with an outer needle inner diameter of 1.07 mm and an inner core outer diameter of 0.7 mm. The spun fibers are placed in a coagulation bath containing 1 wt% tannic acid and 300 mg / L lithium ions. Micro-nano bubbles are introduced through a bubble generator at a working pressure of 0.3 MPa, a gas flow rate of 0.5 L / min, a liquid circulation flow rate of 3 L / min, and a processing time of 20 min. The fibers are then soaked and cured for 12 h, with the supply tank and coagulation bath temperature maintained at 50℃. After high-pressure water jet granulation at 30℃, hollow aluminum-based lithium adsorbent particles with a length of 1-3 mm are obtained. The formed hollow aluminum-based lithium adsorbent particles are rinsed three times with a 300 mg / L lithium ion solution to remove residual organic solvents.

[0056] Example 3 This embodiment provides a method for preparing hydrophilic high-flux aluminum-based lithium adsorbent hollow fiber particles, including the following steps: S1. The precursor of aluminum-based lithium adsorbent was prepared by co-precipitation method. The precursor powder was added to a 5% sodium polyphosphate aqueous solution at a ratio of 60 mL / g and stirred at 40°C for 2 hours. After filtration, it was washed and dispersed with acetone at a liquid-to-solid ratio of 100 mL / g. After filtration, it was dried at 60°C for 12 hours and then ground to obtain highly dispersed aluminum-based lithium adsorbent powder. The aluminum-based lithium adsorbent precursor powder was passed through a 300-mesh sieve.

[0057] S2. Weigh 2 g of polyacrylonitrile, 2 g of polyvinyl chloride, 0.4 g of poly(hydroxyethyl methacrylate) and 0.1 g of silane coupling agent KH550, add them to 15 mL of N,N-dimethylformamide, and heat and stir at 100℃ and 500 rpm until completely dissolved to prepare an adhesive solution.

[0058] S3. Weigh 12 g of highly dispersible aluminum-based lithium adsorbent powder through a 300-mesh sieve and mix it with the binder solution. After stirring and kneading, a shaped material with extrudable plasticity is obtained.

[0059] S4. The shaped material is added to a screw extruder and extruded through a hollow die to obtain a strip-shaped adsorbent preform with a through-hole structure. The extruded hollow strip preform is introduced into a coagulation bath containing 3 wt% tannic acid and 300 mg / L lithium ions. Micro-nano bubbles are introduced into the coagulation bath through a bubble generator. The working pressure of the bubble generator is 0.3 MPa, the gas flow rate is 0.8 L / min, the liquid circulation flow rate is 2 L / min, and the processing time is 10 min. The hollow strip preform undergoes phase transformation and solidification in the coagulation bath to form a through-hole structure. The coagulation bath temperature is maintained at 50℃, and the soaking and solidification is carried out for 12 h. Subsequently, at 30℃, the solidified hollow strip adsorbent is cut into granules to obtain aluminum-based lithium adsorbent hollow particles with a length of 1-3 mm. The formed aluminum-based lithium adsorbent hollow particles are then rinsed three times with a 200 mg / L lithium ion solution to remove residual organic solvents.

[0060] Comparative Example 1 This comparative example provides a method for preparing aluminum-based lithium adsorbent particles, including the following steps: S1. An aluminum-based lithium adsorbent precursor was prepared by co-precipitation method, and the prepared aluminum-based lithium adsorbent precursor powder was passed through a 300-mesh sieve.

[0061] S2. Weigh 2 g of polyvinyl chloride, 2 g of polyacrylonitrile, 0.4 g of poly(dimethylaminoethyl methacrylate) and 0.1 g of aluminate coupling agent F-2, add them to 30 mL of N,N-dimethylformamide, heat and stir at 100℃ and 500 rpm until completely dissolved to prepare an adhesive solution.

[0062] S3. Weigh 12 g of aluminum-based lithium adsorbent powder through a 300-mesh sieve and mix it with the binder solution to prepare a spinning solution. Then, ultrasonically degas the spinning solution for 1 h. Prepare a 300 mg / L lithium ion solution as the spinning core solution.

[0063] S4. The spinning solution is injected into the supply tank of a wet spinning machine and extruded through a coaxial spinning nozzle with an outer needle inner diameter of 1.07 mm and an inner core outer diameter of 0.7 mm. The spun fibers are placed in a coagulation bath containing 1 wt% tannic acid and 300 mg / L lithium ions. Micro-nano bubbles are introduced through a bubble generator at a working pressure of 0.3 MPa, a gas flow rate of 0.8 L / min, a liquid circulation flow rate of 2 L / min, and a processing time of 10 min. The fibers are then soaked and cured for 12 h, with the supply tank and coagulation bath temperature maintained at 50℃. After pelleting at 30℃, hollow aluminum-based lithium adsorbent particles with a length of 1-3 mm are obtained. The formed hollow aluminum-based lithium adsorbent particles are rinsed three times with a 300 mg / L lithium ion solution to remove residual organic solvents.

[0064] Comparative Example 2 This comparative example provides a method for preparing aluminum-based lithium adsorbent particles, including the following steps: S1. An aluminum-based lithium adsorbent precursor was prepared by co-precipitation. The precursor powder was added to a 3% sodium dodecylbenzenesulfonate aqueous solution at a ratio of 60 mL / g and stirred at 60°C for 2 hours. After filtration, the mixture was washed and dispersed with ethanol at a liquid-to-solid ratio of 100 mL / g. After filtration, the mixture was dried at 60°C for 12 hours and then ground to obtain a highly dispersed aluminum-based lithium adsorbent powder. The highly dispersed aluminum-based lithium adsorbent precursor powder was passed through a 300-mesh sieve.

[0065] S2. Weigh 2 g of polyvinyl chloride, 2 g of polyacrylonitrile, 0.4 g of poly(dimethylaminoethyl methacrylate) and 0.1 g of aluminate coupling agent F-2, add them to 30 mL of N,N-dimethylformamide, heat and stir at 100℃ and 500 rpm until completely dissolved to prepare an adhesive solution.

[0066] S3. Weigh 12 g of aluminum-based lithium adsorbent powder through a 300-mesh sieve and mix it with the binder solution to prepare a spinning solution. Then, ultrasonically degas the spinning solution for 1 h.

[0067] S4. The spinning solution is injected into the supply tank of the wet spinning machine and extruded through a spinning nozzle with an inner diameter of 1.07 mm. The spun fibers are placed in a coagulation bath containing 1 wt% tannic acid and 300 mg / L lithium ions. Micro-nano bubbles are introduced through a bubble generator at a working pressure of 0.3 MPa, a gas flow rate of 0.8 L / min, a liquid circulation flow rate of 2 L / min, and a processing time of 10 min. The fibers are then soaked and cured for 12 h, with the supply tank and coagulation bath temperatures maintained at 50℃. After pelleting at 30℃, solid aluminum-based lithium adsorbent fiber particles with a length of 1-3 mm are obtained. The formed solid aluminum-based lithium adsorbent fiber particles are rinsed three times with a 300 mg / L lithium ion solution to remove residual organic solvents.

[0068] Comparative Example 3 This comparative example provides a method for preparing aluminum-based lithium adsorbent particles, including the following steps: S1. The precursor of aluminum-based lithium adsorbent was prepared by co-precipitation method. The precursor powder was added to a 5% sodium polyphosphate aqueous solution at a ratio of 60 mL / g and stirred at 40°C for 2 hours. After filtration, it was washed and dispersed with acetone at a liquid-to-solid ratio of 100 mL / g. After filtration, it was dried at 60°C for 12 hours and then ground to obtain highly dispersed aluminum-based lithium adsorbent powder. The aluminum-based lithium adsorbent precursor powder was passed through a 300-mesh sieve.

[0069] S2. Weigh 2 g of polyacrylonitrile, 2 g of polyvinyl chloride, 0.4 g of poly(hydroxyethyl methacrylate) and 0.1 g of silane coupling agent KH550, add them to 15 mL of N,N-dimethylformamide, and heat and stir at 100℃ and 500 rpm until completely dissolved to prepare an adhesive solution.

[0070] S3. Weigh 12 g of highly dispersible aluminum-based lithium adsorbent powder through a 300-mesh sieve and mix it with the binder solution. After stirring and kneading, a shaped material with extrudable plasticity is obtained.

[0071] S4. The shaped material is added to a screw extruder and extruded through a die to obtain a solid strip-shaped adsorbent preform. The extruded strip-shaped preform is introduced into a coagulation bath containing 3 wt% tannic acid and 300 mg / L lithium ions. Micro-nano bubbles are introduced into the coagulation bath through a bubble generator. The working pressure of the bubble generator is 0.3 MPa, the gas flow rate is 0.8 L / min, the liquid circulation flow rate is 2 L / min, and the processing time is 10 min. The solid strip-shaped preform undergoes phase transformation and solidification in the coagulation bath. The coagulation bath temperature is maintained at 50 ℃, and the solidification is carried out for 12 h. Subsequently, at 30 ℃, the solidified strip-shaped adsorbent is cut into particles to obtain aluminum-based lithium adsorbent particles with a length of 1-3 mm. The solid aluminum-based lithium adsorbent particles are then rinsed three times with a 300 mg / L lithium ion solution to remove residual organic solvents.

[0072] Comparative Example 4 This comparative example provides a method for preparing aluminum-based lithium adsorbent particles, including the following steps: S1. The precursor of aluminum-based lithium adsorbent was prepared by co-precipitation method. The precursor powder was added to a 5% sodium polyphosphate aqueous solution at a ratio of 60 mL / g and stirred at 40°C for 2 hours. After filtration, it was washed and dispersed with acetone at a liquid-to-solid ratio of 100 mL / g. After filtration, it was dried at 60°C for 12 hours and then ground to obtain highly dispersed aluminum-based lithium adsorbent powder. The aluminum-based lithium adsorbent precursor powder was passed through a 300-mesh sieve.

[0073] S2. Weigh 2 g of polyacrylonitrile, 2 g of polyvinyl chloride, 0.4 g of poly(hydroxyethyl methacrylate) and 0.1 g of silane coupling agent KH550, add them to 15 mL of N,N-dimethylformamide, and heat and stir at 100℃ and 500 rpm until completely dissolved to prepare an adhesive solution.

[0074] S3. Weigh 12 g of highly dispersible aluminum-based lithium adsorbent powder through a 300-mesh sieve and mix it with the binder solution. After stirring and kneading, a shaped material with extrudable plasticity is obtained.

[0075] S4. The shaped material is added to a screw extruder and extruded through a die to obtain a solid strip-shaped adsorbent preform. The extruded strip-shaped preform is introduced into a coagulation bath containing 3 wt% tannic acid and 300 mg / L lithium ions, allowing the solid strip-shaped preform to undergo phase transformation and solidify in the coagulation bath. The coagulation bath temperature is maintained at 50 ℃, and the preform is soaked and solidified for 12 hours. Subsequently, the solidified strip-shaped adsorbent is cut into granules at 30 ℃ to obtain aluminum-based lithium adsorbent particles with a length of 1-3 mm. The solid aluminum-based lithium adsorbent particles are then rinsed three times with a 300 mg / L lithium ion solution to remove residual organic solvents.

[0076] Performance testing 1. Product morphology and structure testing The hollow particles of the aluminum-based lithium adsorbent prepared by the technical solution described in Example 1 are as follows: Figure 1 As shown, the particles are white, hollow, cylindrical; their SEM images are shown below. Figure 2 The hollow structure of the aluminum-based lithium adsorbent particles is clearly visible. The loose and porous inner wall of the adsorbent provides a rapid channel for the diffusion of lithium ions inside the particles, which is beneficial to improving the adsorption mass transfer efficiency.

[0077] XRD patterns of the hollow particles of the aluminum-based lithium adsorbents prepared in Examples 1-3 are shown below. Figure 4 As shown in the figure, the diffraction peaks all match the standard card of LiCl·2Al(OH)3·nH2O, indicating that the molding process of the present invention will not damage the crystal structure of the aluminum-based lithium adsorbent.

[0078] 2 Static Adsorption Kinetics Test Static adsorption experiments were conducted on the aluminum-based lithium adsorbent hollow particles prepared in Examples 1-3 and Comparative Examples 1-4, using Chaka Salt Lake brine as the adsorption solution. Chaka Salt Lake brine is a desodium-potassium brine from Chaka Salt Lake in Qinghai Province, and its main cations and their concentrations are shown in Table 1 below. The aluminum-based lithium adsorbent particles and Chaka Salt Lake brine were mixed in an Erlenmeyer flask at a liquid-to-solid ratio of 15 mL / g and placed in a constant-temperature air shaker at 30°C and 180 rpm for adsorption. Samples were taken at regular intervals, and the supernatant was filtered and diluted before the lithium ion concentration was determined by ICP.

[0079] Table 1. Main cations and their concentrations in Chaka Old Brine

[0080] The lithium-ion adsorption capacity of the aluminum-based lithium adsorbent particles at each time point was calculated based on the concentration difference before and after adsorption. This adsorption capacity was calculated using the mass of a unit dry particle as a baseline, and adsorption kinetic curves were plotted as follows: Figure 6As shown, the aluminum-based lithium adsorbent hollow molding materials prepared in Examples 1-3 all exhibited high adsorption performance. Among them, the hollow fiber adsorbents prepared in Examples 1 and 2 had faster adsorption rates, reaching adsorption equilibrium in about 60 minutes, with equilibrium adsorption capacities exceeding 5 mg / g. Although the hollow extruded particles prepared in Example 3 required a relatively longer time to reach equilibrium, their adsorption capacity still remained at a high level.

[0081] The difference between Comparative Example 1 and Example 1 is that the aluminum-based lithium adsorbent precursor was not pretreated with an ionic dispersant and a water-soluble organic solvent. The results showed that the aluminum-based lithium adsorbent particles in Comparative Example 1 exhibited a relatively slow adsorption rate and low adsorption capacity. Therefore, pretreatment of the aluminum-based lithium adsorbent precursor can improve the dispersion performance of the adsorbent powder, ensure sufficient exposure and effective utilization of the adsorption active sites, and thus enhance the adsorption rate and adsorption capacity of the aluminum-based lithium adsorbent.

[0082] The difference between Comparative Example 2 and Example 1 is that coaxial spinning was not used, resulting in solid fiber particles of aluminum-based lithium adsorbent. The results show that the adsorption capacity of the aluminum-based lithium adsorbent particles in Comparative Example 2 was only 4.46 mg / g after 2 hours. This indicates that hollow fiber particles prepared by coaxial spinning can improve porosity and specific surface area, thereby significantly increasing the adsorption capacity of the aluminum-based lithium adsorbent.

[0083] The difference between Comparative Example 3 and Example 3 is that the prepared aluminum-based lithium adsorbent is a solid strip-shaped particle, whose porosity and specific surface area are significantly lower than those of the hollow strip-shaped particles in Example 3. Therefore, the adsorption amount after 2 h is only 2.64 mg / g, which is much lower than that in Example 3.

[0084] The difference between Comparative Example 4 and Example 3 is that no micro / nano bubbles were introduced into the coagulation bath. The results show that the adsorption capacity of the aluminum-based lithium adsorbent prepared in Comparative Example 4 after 2 hours was only 1.82 mg / g, far lower than that of Example 3. This indicates that introducing micro / nano bubbles into the coagulation bath in this invention can significantly improve the surface pore structure of the molded fibers, which is beneficial for forming a porous adsorbent molding material, and thus helps to improve the adsorption capacity of the aluminum-based lithium adsorbent.

[0085] The adsorption-desorption cycles of Examples 1-3 are as follows: Figure 7 As shown in the figure, the hollow aluminum-based lithium adsorbent particles prepared in Examples 1-3 maintained good adsorption performance and lithium ion adsorption capacity of over 5 mg / g after 7 cycles. This indicates that the hollow aluminum-based lithium adsorbent particles prepared in this invention have good cycling stability.

[0086] The above-described embodiments are merely preferred embodiments provided to fully illustrate the present invention, and the scope of protection of the present invention is not limited thereto. Equivalent substitutions or modifications made by those skilled in the art based on the present invention are all within the scope of protection of the present invention. The scope of protection of the present invention is defined by the claims.

Claims

1. A method for preparing hydrophilic high-flux aluminum-based lithium adsorbent hollow fiber particles, characterized in that, Includes the following steps: S1. The aluminum-based lithium adsorbent precursor is stirred evenly in an aqueous solution of an ionic dispersant, filtered, washed and dispersed with a water-soluble organic solvent, and after solid-liquid separation, dried and sieved to obtain a highly dispersible aluminum-based lithium adsorbent precursor powder. S2. Dissolve the non-water-soluble polymer, the water-soluble polymer, and the coupling agent in a water-soluble organic solvent, heat and stir until completely dissolved to obtain an adhesive solution; S3. The highly dispersible aluminum-based lithium adsorbent precursor powder is mixed with the binder solution to obtain a molding slurry; S4. The slurry is extruded through an extrusion molding device or spun into a coagulation bath through a wet spinning molding device and then solidified. After being immersed in a protective liquid and granulated, hydrophilic high-flux aluminum-based lithium adsorbent hollow fiber particles are obtained; wherein, the coagulation bath is an aqueous solution containing a crosslinking agent, lithium salt and micro-nano bubbles.

2. The method for preparing hydrophilic high-flux aluminum-based lithium adsorbent hollow fiber particles according to claim 1, characterized in that, In step S1, the ionic dispersant is one or more of sodium polyphosphate, sodium polyacrylate, sodium dodecylbenzenesulfonate, sodium oleate, fumaric acid, and maleic acid; and / or, In the aqueous solution of the ionic dispersant, the mass fraction of the ionic dispersant is 0.1% to 10%; and / or, The ratio of the aluminum-based lithium adsorbent precursor to the aqueous solution of the ionic dispersant is 0.002~0.5 g / mL; and / or, The stirring speed is 200~1000 rpm, the stirring temperature is 20~90℃, and the stirring time is 0.5~4 hours.

3. The method for preparing hydrophilic high-flux aluminum-based lithium adsorbent hollow fiber particles according to claim 1, characterized in that, In steps S1 and S2, the water-soluble organic solvent is one or more of formamide, N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone, dimethyl sulfoxide, tetrahydrofuran, methanol, ethanol, and acetone.

4. The method for preparing hydrophilic high-flux aluminum-based lithium adsorbent hollow fiber particles according to claim 1, characterized in that, In step S2, the non-water-soluble polymer is one or more selected from polyvinyl chloride, polyvinylidene fluoride, polystyrene, polyacrylonitrile, polymethacrylate, polyethersulfone, polylactic acid, sodium polyacrylate, and polysulfone; and / or, The coupling agent is one of silane coupling agents, titanate coupling agents, aluminate coupling agents, and phosphate coupling agents; The water-soluble polymer is one or more selected from polyacrylamide, polyhydroxyethyl methacrylate, polydimethylaminoethyl methacrylate, gelatin, and carboxymethyl cellulose; and / or, The ratio of the non-water-soluble polymer, the water-soluble polymer, the coupling agent, and the organic solvent is 0.01~0.5 g: 0.01~0.5 g: 0.01~0.2 g: 0.001~0.01 g: 1 mL; and / or, The heating temperature is 40~100℃.

5. The method for preparing hydrophilic high-flux aluminum-based lithium adsorbent hollow fiber particles according to claim 1, characterized in that, In step S3, the ratio of the highly dispersible aluminum-based lithium adsorbent precursor powder to the binder solution is 0.02~1 g / mL; and / or, The mixing process includes one or more of mechanical stirring, ultrasonic dispersion, and degassing, wherein the ultrasonic dispersion time is 30-120 min.

6. The method for preparing hydrophilic high-flux aluminum-based lithium adsorbent hollow fiber particles according to claim 1, characterized in that, In step S4, the crosslinking agent in the coagulation bath is one of citric acid, epichlorohydrin, tannic acid, tartaric acid, glutaraldehyde, borax, calcium ions, or iron ions, with a mass fraction of 1% to 10%; and / or, In the coagulation bath, the lithium salt is one or more of lithium chloride, lithium nitrate, lithium sulfate, or lithium hydroxide, and the lithium ion concentration is 100~500 mg / L; and / or, The micro-nano bubbles are continuously prepared by a micro-nano bubble generator and introduced into the coagulation bath. The operating pressure of the micro-nano bubble generator is 0.1~0.5 MPa, the gas flow rate is 0.1~2.0 L / min, the liquid circulation flow rate is 1~10 L / min, and the processing time is 1~30 min; and / or, The micro-nano bubbles include one or more of the following: air, oxygen, carbon dioxide, nitrogen, argon, and ozone.

7. The method for preparing hydrophilic high-flux aluminum-based lithium adsorbent hollow fiber particles according to claim 1, characterized in that, In step S4, the protective solution is a lithium salt solution, wherein the lithium salt is one or more of lithium chloride, lithium nitrate, lithium sulfate, or lithium hydroxide, and the lithium ion concentration is 100~500 mg / L; and / or, The soaking time is 0.5 to 4 hours, and the soaking temperature is 20 to 80°C.

8. The method for preparing hydrophilic high-flux aluminum-based lithium adsorbent hollow fiber particles according to claim 1, characterized in that, In step S4, when spinning is performed using a wet spinning forming device, the forming slurry is extruded through a coaxial spinning nozzle, and the spinning core liquid is a lithium ion solution.

9. Hydrophilic high-throughput aluminum-based lithium adsorbent hollow fiber particles prepared by the method according to any one of claims 1 to 8.

10. The application of the hydrophilic high-flux aluminum-based lithium adsorbent hollow fiber particles of claim 9 for extracting lithium from lithium-containing solutions, wherein, The lithium-containing solution includes one or more of the following: salt lake brine, seawater, geothermal brine, produced water from oil and gas fields, lithium battery recovery leachate, or self-prepared lithium-containing solution.